Characterization of the Rapid Drop in Pulse Oximetry Reading After Intraoperative Administration of Methylene Blue in Open Thoracoabdominal Aortic Repairs. (November 2019) - Rong, Lisa Q.; Mauer, Elizabeth; Mustapich, Taylor L.; White, Robert S.; Di Franco, Antonino; Girardi, Leonard N.; Gaudino, Mario; Pryor, Kane O.
Abstract : This study evaluates the changes of oxygen saturation (SpO2 ) after intravenous administration of methylene blue in 103 patients undergoing open repair of thoracoabdominal aortic aneurysms. We found that SpO2 decreased by a median (interquartile range [IQR]) of 49% (37%–81%) <1 minute after methylene blue administration and recovered completely after approximately 6 minutes—median (IQR) of 270 seconds (180–510). A shorter time to nadir SpO2 was associated with a higher nadir (Spearman r [95% confidence interval CI], −0.32 [−0.50 to −0.13]; P = .001). Body surface area (BSA) was positively correlated with nadir SpO2 (Spearman r [95% CI], 0.36 [0.15–0.51]; P < .001).